Computational physics of electric discharges in gas flows - Surzhikov, S. T. (De Gruyter studies in mathematical physics, 2012)
Gas discharges are of interest for many processes in mechanics, manufacturing, materials science and aerophysics. To understand the physics behind the phenomena is of key importance for the effective use and development of gas discharge devices. This worktreats methods of computational modeling of electrodischarge processes and dynamics of partially ionized gases. These methods are necessary to tackleproblems of physical mechanics, physics of gas discharges and aerophysics. Particular attention is given to a solution of two-dimensional problems of physical mechanics of glow discharges. The use o.